2021
DOI: 10.3390/cancers13174461
|View full text |Cite
|
Sign up to set email alerts
|

Human DLG1 and SCRIB Are Distinctly Regulated Independently of HPV-16 during the Progression of Oropharyngeal Squamous Cell Carcinomas: A Preliminary Analysis

Abstract: The major causative agents of head and neck squamous cell carcinomas (HNSCCs) are either environmental factors, such as tobacco and alcohol consumption, or infection with oncogenic human papillomaviruses (HPVs). An important aspect of HPV-induced oncogenesis is the targeting by the E6 oncoprotein of PDZ domain-containing substrates for proteasomal destruction. Tumor suppressors DLG1 and SCRIB are two of the principal PDZ domain-containing E6 targets. Both have been shown to play critical roles in the regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Furthermore, a higher expression of SCRIB also predicted shorter survival of ovarian carcinoma [ 24 ] and gastric carcinoma [ 7 ]. However, controversially, the expression of SCRIB was decreased compared to normal tissue in oropharyngeal squamous cell carcinoma, breast cancer, uterine cervical cancer, lung cancer, and lymphoma [ 15 , 38 ]. Therefore, although our results suggest that the expression of SCRIB might be used as a prognostic indicator for CRC patients, further study is needed to determine the clinical significance of SCRIB expression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a higher expression of SCRIB also predicted shorter survival of ovarian carcinoma [ 24 ] and gastric carcinoma [ 7 ]. However, controversially, the expression of SCRIB was decreased compared to normal tissue in oropharyngeal squamous cell carcinoma, breast cancer, uterine cervical cancer, lung cancer, and lymphoma [ 15 , 38 ]. Therefore, although our results suggest that the expression of SCRIB might be used as a prognostic indicator for CRC patients, further study is needed to determine the clinical significance of SCRIB expression.…”
Section: Discussionmentioning
confidence: 99%
“…From each FFPE sample, five to seven slices (10 µm) were used for DNA isolation, utilizing a commercial kit (NucleoSpin ® DNA FFPE XS, Macherey–Nagel, Dueren, Germany) according to the manufacturer’s instructions. The concentration of the isolated DNA was measured using NanoPhotometer ® N60 (Implen GmbH, Munich, Germany), and the quality was validated by PCR using primers generating 99 bp long beta-actin fragments [ 40 , 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…For HPV DNA detection, PCR was performed using short primers suitable for FFPE tissue samples GP5/6 and SPF 10, generating approximately 142 bp and 65 bp long PCR products, respectively [ 42 , 43 ]. PCR amplification was performed as previously described [ 40 , 44 ] and 10 μL of amplified PCR products were run on 3% agarose gels (Sigma Aldrich, St. Louis, MO, USA). A sample was considered to be HPV+ if either the GP5/6 or SPF10 PCR was positive.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that E6 dimerises to enable the degradation of p53 via direct interaction with the ubiquitin ligase E6AP [ 26 , 74 ], suggesting that a similar mechanism may apply to PDZ domain containing proteins that bind to the E6 PBM [ 75 , 76 ]. E6 has also been demonstrated to trigger a relocalisation of Scribble and DLG1 from the cellular membrane into the cytoplasm [ 77 ]. This allows E6 to further stabilise, maintain and increase in infected cells, particularly when binding to Scrib [ 78 , 79 ].…”
Section: Human Papilloma Virus (Hpv) E6 Proteinmentioning
confidence: 99%